Improving Knowledge Of Prebiotic Food Sources Among Pregnant Women To Prevent Anemia - Haslin, Sharfina; Simanjuntak, Netti Meilani; Aritonang, Juneris; Simaremare, Ernawati; Hulu, Lenyi Risdayanti; Lestari, Anisa (Outline Journal of Community Development, 2025)
Anemia during pregnancy remains a significant public health concern, affecting both maternal and fetal health. Adequate intake of prebiotic foods has been suggested as a strategy to improve intestinal health and enhance iron absorption, thereby contributing to anemia prevention. This study aimed to improve pregnant women’s knowledge about prebiotic food sources as a preventive measure against anemia. The intervention employed interactive educational sessions, including lectures, discussions, and demonstrations on the consumption of prebiotic foods. Participants were pregnant women registered at local community health posts or healthcare facilities. Knowledge levels were assessed using structured questionnaires before and after the intervention. The pre-test results indicated that nearly half of the participants (48%) had low knowledge, while only 16% demonstrated high knowledge. Following the educational intervention, knowledge improved significantly, with 68% of participants achieving a high knowledge level and only 8% remaining in the low category. These findings indicate that targeted educational programs on prebiotic food consumption effectively enhance pregnant women’s understanding of anemia prevention. Increasing awareness and knowledge about prebiotic foods can encourage healthier dietary practices, ultimately contributing to a reduction in anemia prevalence during pregnancy.